How Biofilm Growth Affects Candida-Host Interactions - Eix, Emily F.; Nett, Jeniel E. (Frontiers in Microbiology, 2020)
Candida spp. proliferate as surface-associated biofilms in a variety of clinical niches. These biofilms can be extremely difficult to eradicate in healthcare settings. Cells within biofilm communities grow as aggregates and produce a protective extracellular matrix, properties that impact the ability of the host to respond to infection. Cells that disperse from biofilms display a phenotype of enhanced pathogenicity. In this review, we highlight host-biofilm interactions for Candida, focusing on how biofilm formation influences innate immune responses.